Atlas of Robotic Urologic Surgery - Su, Li-Ming (Springer International Publishing : Imprint: Springer, 2017)
As a consequence of rapid changes in surgical technique and incorporation of new robotic technology and advanced intraoperative imaging, the second edition of this important textbook reflects these rapid changes in the field of robotic urologic surgery. The goals of this textbook are three-fold. First, it provides a comprehensive update on surgical techniques pertinent to each robotic urologic procedure being performed worldwide, spanning procedures performed for both upper urinary tract (e.g. adrenal, kidney, ureter) and lower urinary tract (e.g. bladder, prostate, seminal vesicle, vagina) as well as adult and pediatric conditions. Second, advances in new robotic instruments and technology as well as advanced intraoperative imaging modalities used for surgical navigation are incorporated. Third, to further improve upon the first edition, this textbook is highly illustrated with schematic drawings to aid an understanding of the surgical techniques. Links to online video content is presented throughout. Atlas of Robotic Urologic Surgery will serve as a vital step-by-step, highly illustrated comprehensive yet concise resource to urologic surgeons, trainees and robotic surgical assistants embarking on robotic surgery as part of their surgical armamentarium for treatment of urologic diseases.
Keywords: Medicine.; Minimally invasive surgery.; Urology.; elektronické knihy; electronic books